A method of planning and designing transmission networks for government and enterprises based on a rectangle-like distribution model combined with heat maps - Shuchong NAN; Cheng CHEN; Xunbiao LIAN; Han WANG (Dianxin kexue)
The circuit direction and service access point of the special line service for government enterprise group customers are decided by the customers themselves, and the service opening is extremely unpredictable.In order to effectively solve the problems of strong subjectivity, difficult adjustment, long cycle and low efficiency in the service opening of government and enterprise customers, a typical simulation environment and a quasi rectangular distribution model was built, and two deployment strategies combined with the thermal map were proposed.The simulation analysis shows that under the same conditions, the number of VC-OTN (VC cross connecting function with optical transport network) points meeting the coverage requirements decreases with the increase of the maximum access distance, the client point coverage increases with the increase of the deployed VC-OTN points, and the deployment benefit of strategy 2 (group coverage by maturity) is higher than that of strategy 1 (priority coverage of hot spots).When the coverage requirements are met, the number of VC points required by the theoretical minimum, strategy 1 and strategy 2 are 26, 58 and 50, respectively.This method provides reliable theoretical guidance for the accurate and rapid construction of network system, avoids blind deployment, improves the accuracy of deployment planning, and provides construction reference ideas for the subsequent construction of urban VC-OTN nodes.